Cyathealean Antarctic ferns from the Aptian Cerro Negro Formation: Rafaherbstia nishidai gen. et sp. nov. and associated fertile organs - Vera, Ezequiel Ignacio; Cesari, Silvia Nelida (Review of Palaeobotany and Palynology)
New remains corresponding to Cyathealean tree ferns are described for the Aptian Cerro Negro Formation at Byers Peninsula, Livingston Island (South Shetland Islands, Antarctica). A new genus and species, Rafaherbstia nishidai, is proposed for several permineralized dictyostelic stems characterized by a heterogeneous pith with a central star-shaped sclerenchyma mass, U-shaped meristeles developing small hooks at the margins of the leaf gap, sclerenchyma sheaths surrounding the vascular strands, and leaf traces omega-shaped and multi parted. The new taxon shows a combination of features that preclude its placement in one of the eight recognized families of Cyatheales, supporting that previous diversity of tree ferns was higher than in modern times. Fragmentary isolated sori with preserved sporangia containing trilete spores, recovered from the sedimentary matrix surrounding the stems, are also described. These new tree ferns increase the diversity of Cyatheales in the Cerro Negro Formation, and support warm climatic conditions in this region during the Aptian. Fil: Vera, Ezequiel Ignacio. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Geología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Cesari, Silvia Nelida. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina